Multisensory attention and tactile information-processing - Spence, C (Elsevier, 2002)
Although a great deal is now known about the peripheral sensory mechanisms involved in tactile information processing [Ann Rev Psychol 1990;50:305], it is only more recently that we have started to gain a clearer understanding of the effects of selective attention on tactile perception [Front Biosci 2000;5:D894]. To date, the majority of this selective attention research has considered each modality in isolation. However, in order to deal with the multimodal selection problems of everyday life, we need to be able to coordinate our selective attention cross-modally [Philos Trans R Soc, Sec B 1998:353; Curr Biol 2000;10:R731]. In this review, I will highlight the results of behavioral studies demonstrating the existence of extensive cross-modal links in selective attention between touch, vision, audition, and even olfaction. In particular, the review is structured around two key research questions: First, “Can attention can be selectively directed to a particular sensory modality?”, and second “Are there cross-modal links in spatial attention?”. The results of recent neuroimaging studies that have started to elucidate some of the neural mechanisms underlying these cross-modal attentional effects are also discussed, and potential questions for future research outlined.